Clinical imaging features of cerebral amyloid angiopathy - Boulouis, Grégoire (Henry Stewart Talks, 2023)
Cerebral amyloid angiopathy (CAA), Clinical imaging, Clinical reasoning, Biomarkers, Hemorrhagic biomarkers in CAA, Cerebral microbleeds, Cortical superficial siderosis, Convexity subarachnoid hemorrhage, Boston 2.0 criteria, Lobar intracerebral hemorrhage, White matter hyperintensities, Mixed locations hemorrhages, Cerebellar hemorrhages, Cortical micro-infarcts, Edinburgh criteria